2014
DOI: 10.1002/pbc.25135
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function after hematopoietic cell transplantation: An echocardiographic cross‐sectional study in young adults treated in childhood

Abstract: Almost two decades after HCT, including preparative regimens with TBI, cardiac function in patients was found to be within normal range. However, when compared with a healthy control group, patients after HCT showed lower systolic and diastolic left ventricular function as well as lower right ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…36 We have previously shown that although several echocardiographic variables were significantly decreased compared with those of healthy control subjects in long-term survivors after HCT, cardiac function was nevertheless comparatively well preserved with all echocardiographic variables within the normal range. 9 It is therefore not surprising that we found no significant associations between W peak , which was clinically significantly decreased, and echocardiographic variables, which were not.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…36 We have previously shown that although several echocardiographic variables were significantly decreased compared with those of healthy control subjects in long-term survivors after HCT, cardiac function was nevertheless comparatively well preserved with all echocardiographic variables within the normal range. 9 It is therefore not surprising that we found no significant associations between W peak , which was clinically significantly decreased, and echocardiographic variables, which were not.…”
Section: Discussionmentioning
confidence: 59%
“…Results from the study have been previously reported. 9,12,17,22 Forty-five children younger than 18 years and 1 patient who was 18.3 years old, with ALL (n = 43) or LBL (n = 3), were treated at Uppsala University Children's Hospital between October 1985 and June 1999 with autologous (n = 31), syngeneic (n = 1), or allogeneic (n = 14) HCT, which included TBI. Of these 46 patients, 29 were alive at the time of inclusion between 2006 and 2009 (autologous/syngeneic, n = 22, allogeneic, n = 7).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, diastolic dysfunction and restrictive cardiomyopathy from pre‐HSCT insults may lead to earlier symptomatic heart failure in those with systolic dysfunction. Long‐term survivors of pediatric HSCT have rates of LVSD between 0 and 26% due in part to nonstandardized monitoring intervals and variable definitions of LVSD . Effects of cardiotoxic therapies may be too subtle to be detected by traditional echocardiography and only become evident (e.g., reduction in ejection fraction) once significant cardiac reserves are depleted .…”
Section: Defining Cardiac Injurymentioning
confidence: 99%